Screening for DSM‐IV‐TR cognitive disorder NOS in Parkinson's disease using the Mattis Dementia Rating Scale. (24th May 2012) - Pontone, Gregory M.; Palanci, Justin; Williams, James R.; Bassett, Susan Spear
<x xml:space="preserve">Abstract</x> Objective This study explores the utility of the Mattis Dementia Rating Scale (MDRS) as a screening tool for the Diagnostic and Statistical Manual for Mental Disorders 4th edition (DSM‐IV‐TR) diagnosis cognitive disorder not otherwise specified (NOS) in Parkinson's disease (PD). Methods A total of 125 individuals with PD were diagnosed using DSM‐IV‐TR criteria for cognitive disorder NOS and dementia. Receiver operating characteristics (ROC) tested the discriminant validity of the MDRS, with the clinician's diagnosis serving as the gold standard. Results The MDRS ROC curve to discriminate subjects with cognitive disorder NOS from non‐demented subjects had an area under the curve of 0.59 (standard error = 0.08, 95% CI: 0.43–0.74). Conclusions The MDRS is not effective for identifying PD patients with cognitive disorder NOS without dementia. Copyright © 2012 John Wiley & Sons, Ltd.